2011
DOI: 10.1097/pcc.0b013e3181e2a596
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of renal function and survival after continuous renal replacement therapy during extracorporeal membrane oxygenation*

Abstract: Objective To assess the outcome of pediatric patients supported by concomitant extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT). Design, Setting, and Patients Acute kidney injury (AKI) is associated with mortality in ECMO patients. CRRT on ECMO provides an efficient and potentially beneficial method of AKI management. Concern that concomitant CRRT use increases the risk of developing anuria and chronic renal failure (CRF) limits its use in some centers. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 25 publications
(34 reference statements)
7
104
0
1
Order By: Relevance
“…Additional reviews of institutional experiences with CRRT and ECMO described the technical challenges and complications associated with continuous venovenous hemofiltration (CVVH) and ECMO using objective clinical and/or biochemical markers (9,16). Recently, Paden et al (19), suggested that the combination of CVVH and ECMO does not contribute to development of chronic renal failure but is associated with higher mortality risk than ECMO alone, probably because of the preexisting renal failure rather than the introduction of CVVH. In addition, Santiago et al (20) analyzed the efficacy and safety of the inclusion of CRRT with ECMO in vitro, in a piglet model, as well as in selected pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reviews of institutional experiences with CRRT and ECMO described the technical challenges and complications associated with continuous venovenous hemofiltration (CVVH) and ECMO using objective clinical and/or biochemical markers (9,16). Recently, Paden et al (19), suggested that the combination of CVVH and ECMO does not contribute to development of chronic renal failure but is associated with higher mortality risk than ECMO alone, probably because of the preexisting renal failure rather than the introduction of CVVH. In addition, Santiago et al (20) analyzed the efficacy and safety of the inclusion of CRRT with ECMO in vitro, in a piglet model, as well as in selected pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients receiving ECMO who require CRRT is especially poor [15,16,17]. Wu et al [13] reported that the latency between hospital admission and dialysis correlated with reduced survival among patients who received acute dialysis during ECMO therapy, especially those who had not undergone coronary artery bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Paden et al [11] in his study of 154 patients on ECMO and CRRT showed that renal recovery was seen in 96% of the patients who survived. Similarly, Meyer et al [12] in a series of neonatal and pediatric survivors renal recovery was seen in 14/15 (93%) patients.…”
Section: Renal Recovery and Combined Ecmo-crrtmentioning
confidence: 99%